Role of Cardiac IKs Current in Repolarization Reserve Process During Late Sodium Current (INaL) Activation - Printemps, Richard; Salvetat, Céline; Faivre, Jean-françois; Grand, Marie Le; Bois, Patrick; Maati, Hamid Moha ou (Cardiology and Cardiovascular Medicine, 2019)
The slow delayed rectifier K+ current (IKs) mediated by KCNQ1/KCNE1 channels contributes to the cardiac action potential in human and other species. Several studies have shown that IKs protects the heart from excessive action potential prolongation induced by the rapid delayed rectifier K+ current (IKr) inhibition. Moreover, several studies have shown that combined pharmacological inhibition of IKs and IKr currents increases cardiac parameters such as instability and dispersion of repolarization, and short term QT interval variability. It is known these effects promote a high risk of occurrence of « torsade de pointes ». However, the consequences of combined IKs current inhibition with an increase of the late sodium current (INaL) on cardiac repolarization has not been studied and reported in the literature. The aim of this work is to study the effects of pharmacological inhibition of IKs with chromanol 293B, a reference inhibitor of IKs current, during action potential prolongation promoted by INaL pharmacological activation by veratridine. These effects were also evaluated in the presence of doxorubicin, an anticancer drug increasing cardiac ventricular repolarisation and QT interval duration. Methods Involvement of IKs current in repolarization reserve process was studied in the presence of INaL current activated by veratridine on Guinea pig papillary muscle and isolated perfused heart using intracellular microelectrode and Langendorff techniques. Action potentials (AP) and Electrocardiogram (ECG) were recorded in the presence of veratridine alone and in the presence of veratridine and chromanol 293B or doxorubicin. The IKs current inhibition was previously evaluated on HEK-293/KCNQ1-KCNE1 stable cell line by chromanol 293B (supplemental Figure 1) and doxorubicin (Previous work). Results Our results show that the IKs current is in